Deradicalization programs in Indonesia: Bibliometric analysis of international publication trends from 1980 to 2022 - Gonda Yumitro; Rizki Febriani; Ali Roziqin; Nurdiana Abiyogha (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2022)
This study discusses about deradicalization in Indonesia with a bibliometric approach. The data presented in this study used the Scopus database and were visualized using the VOSviewer. The data collected were obtained by searching with the keywords